COGNITIVE PROCESSES IN WRITING OF TENTH GRADE STUDENTS AT A SENIOR HIGH SCHOOL - Johannes Jefria Gultom; Doni Setiawan Sinaga (LINGUISTIK TERAPAN, 2023)
The aim of this study was to describe the cognitive processes in writing of tenth grade students. The research was conducted in descriptive qualitative design. There were 15 students involved in this research. The data in this study were the students’ writing descriptive paragraph which showed their cognitive processes in planning, translation and reviewing their writing. The data source was taken from the results of the task of writing a descriptive text for tenth grade students at SMAS Amir Hamzah Medan. The finding in the study was that the students tended to compose an outline as a plan and visualize ideas based on their memory and writing abilities. Further, in the process of rewriting they did rewriting by revising the mistakes in their previous writing.